2008
DOI: 10.2174/1874318808002010068
|View full text |Cite
|
Sign up to set email alerts
|

Equine Herpes Virus-1: Virus, Immunity and Vaccines

Abstract: Equine Herpes virus-1 (EHV-1) is one of the most common respiratory pathogens of the horse. EHV-1 induces several clinical signs of disease ranging in severity, from mild respiratory distress to abortion in pregnant mares, neonatal foal death and neuropathogenic disorders. This review details some aspects of EHV-1 biology, its life cycle and pathogenicity in the natural host. Protective immunity stimulated by natural EHV-1 infection, which is short lived and depends of both humoral and cellular immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 131 publications
0
19
0
2
Order By: Relevance
“…In its target host, it induces mild respiratory diseases, abortion, neonatal foal death, and neuropathogenic disorders. Like the other α-herpesviruses (HSV-1, BHV-1, PRV), EHV-1 infection is characterized by neurotropism and the ability to establish latent infections in trigeminal ganglion neurons [3, 16, 17, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…In its target host, it induces mild respiratory diseases, abortion, neonatal foal death, and neuropathogenic disorders. Like the other α-herpesviruses (HSV-1, BHV-1, PRV), EHV-1 infection is characterized by neurotropism and the ability to establish latent infections in trigeminal ganglion neurons [3, 16, 17, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…EHM incidence has increased in most parts of the world, in Europe and North America, as well as in Oceania, Africa, and Asia [10,11,28]. Pathogenesis and clinical disease: After primary replication in the respiratory tract, EHV-1 disseminates via cell-associated viremia in peripheral blood mononuclear cells and subsequently infects the endothelial cells of the pregnant uterus or central nervous system, leading in some cases to abortion and/or neurological disorders [34]. The incubation period of the disease is 6-8 days (before neurological signs become apparent), both in experimentally and in naturally EHV-1-infected horses [35].…”
Section: Equid Herpesvirusesmentioning
confidence: 99%
“…Experimental infections with recombinant viruses performed by Goodman et al (2007) demonstrated that the N752 sequence variant of EHV-1 DNA Pol, when compared to the D752 variant, generated a low level of viremia in natural hosts and presented with reduced overall pathogenicity and capacity to induce neurological signs [46]. The discovery of this single polymorphism in ORF30 led to the development of a SNP-PCR (SNP-single nucleotide polymorphism) test for the detection Pathogenesis and clinical disease: After primary replication in the respiratory tract, EHV-1 disseminates via cell-associated viremia in peripheral blood mononuclear cells and subsequently infects the endothelial cells of the pregnant uterus or central nervous system, leading in some cases to abortion and/or neurological disorders [34]. The incubation period of the disease is 6-8 days (before neurological signs become apparent), both in experimentally and in naturally EHV-1-infected horses [35].…”
Section: Equid Herpesvirusesmentioning
confidence: 99%
“…Até o momento já foram identificadas 14 espécies de herpesvírus que acometem os equídeos (KLEIBOEKER et al, 2004;EHLERS et al, 2008;PAILLOT et al, 2008;OSTERRIEDER et al, 2010;KING et al, 2011) Fonte dos dados brutos: King et al (2011) Conforme já foi citado, o EHV-1 é o agente causador de diferentes formas de doença em cavalos, das quais as mais comuns são a rinopneumonite, caracterizada por manifestações respiratórias no trato superior em animais jovens; o abortamento a vírus, responsável pelo abortamento em éguas no terço final da gestação (entre o 8 o e o 11 o meses) e mortalidade perinatal em potros e a EHM, caracterizada por manifestações neurológicas em cavalos adultos. Além disso, e ainda que com menor frequência, o EHV-1 pode provocar doenças oculares e infecção pulmonar vasculotrópica.…”
Section: Isolamento Viral E Identificaçãounclassified
“…A partir de estudos que utilizaram camundongos knockout (CCL3 / ), infectados pelo EHV-1, foi comprovado que a quimiocina CCL3 (proteína inflamatória de macrófagos 1 alfa) desempenha papel fundamental no controle da replicação viral nos pulmões por meio do desencadeamento de intensa resposta inflamatória (VAN DE WALLE et al, 2008a,b). (PAILLOT et al, 2005;PAILLOT et al, 2007;PAILLOT et al, 2008 A quimiocina CCL2 está envolvida nos mecanismos de eliminação viral atuando diretamente na permeabilidade da barreira hematoencefálica e/ou como fator quimiotático para linfócitos e macrófagos no processo inflamatório do SNC (STAMATOVIC et al, 2005;DESHMANE et al, 2009). A expressão gênica de CCL2 no tecido nervoso dos camundongos C57BL/6, CD4 / e CD8 / infectados pelo EHV-1 aumentou expressivamente, observado-se valores variando de 4 a 7 mil e 16 a 32 mil vezes maiores do que os controles no 2º e 3º dpi, respectivamente.…”
Section: Ehv-1 A9/92unclassified